PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL NUMBER HEAD TOGETHER (NHT) DI SEKOLAH DASAR: PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL NUMBER HEAD TOGETHER (NHT) DI SEKOLAH DASAR - megawati nurlev avana (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
This research is motivated by the problem of the process and learning outcomes of students in learning mathematics in Class V SD Negeri 101/II Muara Bungo is still low, as evidenced by the results of initial observations, of 43 students only 15 (35%) students who meet the KKM. The reason is that educators still dominate learning by using the lecture method, so that it is less attractive to students to learn. The purpose of this study was to describe the application of the NHT model in improving the process and learning outcomes of mathematics in class V. The type of research used in this study was CAR. This research was carried out in two cycles, each cycle consisting of two meetings. Data collection techniques used observation, and learning outcomes tests, while data analysis used quantitative and qualitative approaches. The results showed that: (1) in the first cycle the application of the NHT model in the learning process of the educator aspect reached 88% and the student aspect reached 72%. While in the second cycle there was an increase in the aspect of educators 94% and aspects of students 88%. (2) In the second cycle the application of the NHT model, the students' learning outcomes reached 70% completeness and in the second cycle they increased to 84%. Based on the results of the study, it can be concluded that the process and learning outcomes of fifth grade mathematics at SD Negeri 101/II Muara Bungo can be improved through the use of the NHT model.